2014
DOI: 10.1038/modpathol.2013.210
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for HLA-A typing in formalin-fixed paraffin-embedded-derived DNA

Abstract: The aim of this study was to establish a novel approach for human leukocyte antigen (HLA)-typing from formalin-fixed paraffin-embedded-derived DNA. HLAs can be a prognostic factor in cancer and have an extensive polymorphism. This polymorphism is predominantly restricted to exons, which encode the peptidebinding domain of the protein. Formalin-fixed paraffin-embedded material is routinely collected in the clinic and therefore a great source of DNA for genetic analyses. However, its low quality due to fragmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 22 publications
(31 reference statements)
2
14
0
Order By: Relevance
“…As at times, HLA alleles only vary at the singlenucleotide level, some changes brought about by FFPE processing, such as DNA fragmentation or the presence of nucleotide changes, might have contributed to the lower sequencing accuracy in this sample type. A previous study demonstrated the amplification of exons 2, 3, and 4 of HLA-A in only 88% (14/16) from DNA isolated from 10-year-old FFPE tissue samples (36). Among the 5 algorithms included in our study, the performance of HLA-HD was consistent for the WBC, plasma, and tissue samples, which were highly concordant with the SBTbased HLA genotype.…”
Section: Ngs Typically Generates Short Read Lengths (Betweensupporting
confidence: 73%
“…As at times, HLA alleles only vary at the singlenucleotide level, some changes brought about by FFPE processing, such as DNA fragmentation or the presence of nucleotide changes, might have contributed to the lower sequencing accuracy in this sample type. A previous study demonstrated the amplification of exons 2, 3, and 4 of HLA-A in only 88% (14/16) from DNA isolated from 10-year-old FFPE tissue samples (36). Among the 5 algorithms included in our study, the performance of HLA-HD was consistent for the WBC, plasma, and tissue samples, which were highly concordant with the SBTbased HLA genotype.…”
Section: Ngs Typically Generates Short Read Lengths (Betweensupporting
confidence: 73%
“…For amplification, the following oligonucleotide primers were designed according to a protocol published in ref. 41 : A2-2F: 5′-TCTCAGCCACTCCTCGTC-3′, G-R: 5′-TGTCGAACCGCACGAACTG-3′. After amplification according to ref.…”
Section: Methodsmentioning
confidence: 99%
“…After amplification according to ref. 41 , Sanger sequencing was performed, and the nucleotide at nucleotide position 78 of the HLA-A gene locus (reference sequence NM_001242758.1) was used for classification, GCTC Y CACT with T indicating HLA-A*02:01 and C indicating non-HLA-A*02:01. The method was successfully validated in independent specimens with known HLA type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product of the cDNA synthesis was subsequently taken for a SYBR-Green based qPCR, as previously described by Lindquist et al (9). The following genes were examined: HPV16 E5, E7, with primers as described in Ramqvist et al (29) and HLA-A for exon 3 with primers as described by Villabona et al (30). GUS B was added as an endogenous control.…”
Section: Flow Cytometry For Evaluation Of Hla Class I Expression Celmentioning
confidence: 99%